A quantum chemistry background of sickle cell anemia and gaps in antisickling drug development - Suhail, Mohammad; Usmani, Safwana; Ahmad, Mehmood (European Journal of Chemistry, 2023)
Sickle cell anemia disease has been a great challenge for the world in the present situation. It occurs only due to the polymerization of sickle hemoglobin (HbS) having Pro-Val-Glu (PVG) typed mutation, while the polymerization does not occur in normal hemoglobin (HbA) having Pro-Glu-Glu (PGG) residues. According to data from the literature, Val-beta6 of Pro-Val-Glu is hydrophobic in nature, which appears to fit into a hydrophobic pocket in the adjacent HbS. After the insertion of Pro-Val-Glu into a hydrophobic pocket on the adjacent HbS, the polymerization is started. This is a questionable point on how the replacement of glutamic acid with valine in HbS makes it more reactive to fit into a hydrophobic pocket on adjacent HbS for polymerization. No data from the literature on the reactivity of HbS for polymerization was found yet. This is the first time that the theoretical calculation was done in both HbA and HbS where they were structurally different. After that, a comparative study between PVG and PGG was done at quantum level for the evaluation of the reactivity to fit into a hydrophobic pocket on adjacent HbS. At a quantum level, it was found that the HOMO-LUMO gap of Pro-Val-Glu was lower than that of Pro-Glu-Glu. According to the data from the literature, the lesser HOMO-LUMO gap promotes the initiation of the polymerization reaction. On the basis of the results, it was also shown how the mutation point (Pro-Val-Glu) in HbS becomes more reactive to polymerization, whereas Pro-Glu-Glu in HbA does not. The computational method developed for the first time will be very helpful not only for molecular biologists but also for computational and medicinal chemists. Additionally, the required modifications based on gaps in anti-sickling drug development are also suggested in the presented article.